Challenging acts of international organizations before national courts - Reinisch, August (Oxford : Oxford University Press, 2010)
An increasing number of challenges against the activities and decisions of international organisations are brought before national courts. This book offers an overview of how different courts have dealt with these cases and an analysis of the legal framework which applies to them, identifying common ground across jurisdictions.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 17, 2010).
Keywords: International agencies; International and municipal law; Jurisdiction